Smart hydroponic system - Rahut, Saikat; Sadia, Nowshin; Nipa, Azmin Akter; Rahman, Rokaia (Brac University, 2023)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.